Konvektivni prenos toplote v vrtečem kanalu kaskade z ravnimi lopaticami - Mori, Mitja (Strojniški vestnik, 2003)
In this paper we present a numerical approach to determining the variation of rotational speed with the convective heat transfer of blade structures. The investigated structure, which is cooled by air, was subjected to an axial hot-air stream in a cross-flow system. In order to exclude the influence of undesirable, aerodynamic flow forces, a simplified geometry was chosen, and the influence of varying the rotational speed was studied. The distributions of heat-transfer rate on the hot side of the structure's wall were determined with CFD calculations. The non-uniformity of the heat transfer increased with the rotational speed due to the increasing impact of centrifugal flow forces on the boundary-layer thickness. The impact of rotational speed on the heat-transfer rate was found not to be significant. The results of the studiedstructure were also used to validate various one-dimensional, empirical, convective heat-transfer models that are commonly applied in engineering practice. In all cases, the flat-wall heat-transfer treatment showed the best agreement with the results of the CFD calculations.
Keywords: turbine plinske; hlajenje konvektivno; števila Nusselt; analize numerične; prenos roplote; plinske turbine; numerična analiza